ONLINE LEARNING PERCEPTIONS AND EXPERIENCES: A MIXED METHODS STUDY ON THE ECONOMICS EDUCATION STUDENTS IN AN ONLINE BUSINESS COMMUNICATION COURSE - Nurwahida Nurwahida; Rahmawati Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Online learning has been evolving profoundly and as a result, altering students’ ways in developing their competencies in business competencies.The study seeks to analyze how students perceive and experience the delivery of an online Business Communication course taking place at one of the Economics Education Programs in South Sulawesi, aiming to evaluate its effectiveness. Employing a mixed methods approach, the study engaged 55 participants through surveys and involved 8 participants in interviews, to unravel students’ experiences with online learning. The findings pinpoint students’ approving attitudes in terms of flexibility and time efficiency enhancement concerning the use of digital learning tools. The results, however, also reveal obstacles such as technical issues and social interaction constraint. Students’ experiences in an online learning vary depending on the degree of their participation and adaptability, and their learning motivation and satisfaction are encouraged by lecturers and peers’ proactive engagement. The study results establish the pivotal roles of consequential perceptions of technological integration, academic interaction significance, and consecutive pedagogical guidance in establishing successful online Business Communication course. The study further contributes theoretically to the advancement of experience-oriented learning models and practically to the educators and institutions in building interactive, reflective and contextually adaptive spaces.